The Law Enforcement of Illegal Fishing in the Perspective of UNCLOS 1982: The Case of Illegal Fishing in the North Natuna Sea - Gunawan, Yordan; Amirullah, Muhammad Nur Rifqi; Abdussalam, Muhammad Rafi; Permana, Vensky Ghaniiyyu Putri (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
The potential for illegal fishing in Indonesia's marine areas is tremendous, especially in the exclusive economic zone of Indonesia, mainly in the North Natuna marine area. Following the rampant illegal fishing activities, policies on preventing and eradicating illegal fishing in the Republic of Indonesia are constantly debated both in theory and implementation. Illegal fishing activities are not only a problem for Indonesia but also a cross-border problem because the perpetrators come from across countries. Therefore, the handling of this problem must be cross-border, and the implementation of international law is necessary. By using normative legal research, the paper analyzed the law enforcement of illegal fishing by referring to UNCLOS as the basis of international maritime law to obtain legal certainty in illegal fishing in the Indonesian exclusive economic zone (EEZ), especially in the North Natuna Sea area. According to Article 73 paragraph (1) UNCLOS 1982, Indonesia can take action against illegal fishing perpetrators by using its own legal regulations because illegal fishing can interfere with the management rights of Indonesia's marine natural resources.